2015
DOI: 10.1371/journal.pntd.0003733
|View full text |Cite
|
Sign up to set email alerts
|

A Household Serosurvey to Estimate the Magnitude of a Dengue Outbreak in Mombasa, Kenya, 2013

Abstract: Dengue appears to be endemic in Africa with a number of reported outbreaks. In February 2013, several individuals with dengue-like illnesses and negative malaria blood smears were identified in Mombasa, Kenya. Dengue was laboratory confirmed and an investigation was conducted to estimate the magnitude of local transmission including a serologic survey to determine incident dengue virus (DENV) infections. Consenting household members provided serum and were questioned regarding exposures and medical history. RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
80
1
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(89 citation statements)
references
References 36 publications
(33 reference statements)
6
80
1
2
Order By: Relevance
“…Its detection in febrile Kenyan adults sampled for this study is also consistent with its detection in an outbreak reported from Mombasa, Kenya in 2013 (Ellis et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…Its detection in febrile Kenyan adults sampled for this study is also consistent with its detection in an outbreak reported from Mombasa, Kenya in 2013 (Ellis et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…aegypti [65,66]. This likely explains the widespread occurrence of dengue cases across the city this time [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The distribution of dengue vectors and several other factors including rapid population growth, unplanned urbanization, and increased international travel increase the risk of dengue transmission [16]. Indeed, over the past 5 decades, dengue cases have been reported in many countries in sub-Saharan Africa [10] including European travelers returning from Tanzania, Zanzibar, the Comoros, Benin, Cape Verde, Gunea Bisau and Senegal [17–20] and the 2011–2013 outbreaks in Angola and Kenya [21,22]. This apparent emergence of DENV in most of Africa might be due to increased awareness of the disease, availability of better diagnostic tests, and improved access to specialized laboratory facilities [23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Kenya, the first dengue outbreak was reported in 1982 [6], with more recent outbreaks reported in Mombasa [7] and the northeastern town of Mandera [8]. These recent dengue outbreaks involved three different dengue virus (DENV) serotypes (DENV-1, DENV-2 and DENV-3) [7, 8].…”
Section: Introductionmentioning
confidence: 99%